Clinical applications of optical coherence tomography angiography - Agnifili, Luca (ESASO course series / series editors F. Bandello, B. Corcóstegui, 2020)
The recent introduction of optical coherence tomography angiography (OCTA) has remarkably expanded the knowledge of different retinal, chorioretinal, and optic disc disorders. OCTA is nowadays often used as a routine exam in clinical practice, which has significantly modified the approach to patients, granting the opportunity to easily and noninvasively investigate the retinal and choroidal circulation. Major experts in posterior eye imaging share in this publication their experiences, images and ideas using OCTA in various contexts including age-related macular degeneration, diabetic retinopathy and retinal dystrophies, thus providing an in-depth overview of the latest knowledge in this field.